Effects of functionalized graphene oxide modified sizing agent on the interfacial and mechanical properties of carbon fiber reinforced polyamide 6 composites. Issue 11 (5th September 2022) - Cai, Guangbin; Yan, Chun; Liu, Dong; Xu, Haibing; Lu, Jiateng; Chen, Gang; Chen, Mingda; Zhu, Yingdan
Abstract: In this study, a novel functionalized graphene oxide (F‐GO) modified polyamide 6 (PA6) sizing agent is developed to improve the interfacial and mechanical properties of carbon fiber (CF) reinforced PA6 composites. To enhance compatibility between GO and sizing agent, PA6 molecular chains are covalently grafted onto the GO sheets in advance. The results show that the F‐GO modified sizing layer improves interfacial compatibility and wettability of the CF surface. Moreover, F‐GO nanoparticles retard crack propagation along the interface based on the reinforcement effect. Accordingly, the interfacial shear strength increases by 54.5% from 45.1 MPa for desized CF/PA6 composites to 69.7 MPa for F‐GO modified sizing agent treated CF/PA6 composites. Meanwhile, the average interlaminar shear strength, tensile strength, and flexural strength increase by 45.2%, 15.6%, and 19.3% from 45.7, 1307.4, and 792.2 MPa for desized CF/PA6 composites to 66.3, 1511.2, and 945.2 MPa for those reinforced with the CFs treated by the F‐GO modified sizing agent due to the effective stress transfer across the interface. The improvement in the mechanical properties is verified based on the cross‐section morphology and fracture surfaces. Abstract :